Remote Preparation of Three-Particle GHZ-Class States (Journal of Atomic and Molecular Sciences, 2010)
A scheme is presented for remote state preparation of three-particle GHZ-class states by using a Bell state and an asymmetric W state as the quantum channel. In the scheme, the success probability of preparation and classical communication cost are calculated. In general, Bob can successfully prepare the initial state with the probability 1/4 and consume 1/4 classical bits. However, in special situations the success probability of preparation can reach 1/2 or even 1 after consuming a little additional classical bits.